Cerebral venous sinus thrombosis as the initial presentation of essential thrombocythemia - A case report and literature review - Qudsum Yousaf (17563245) (2022)
Myeloproliferative disorders (MPD) are associated with vascular thrombosis. Common sites for thrombosis are large arteries; however, less commonly, cerebral venous sinus thrombosis (CVST) has also been reported. It is rare to have CVST as an initial presentation of MPD. We discuss a male patient in whose presentation due to CVST led to the diagnosis of essential thrombocythemia (ET). Furthermore, we performed a literature review to evaluate the association of CVST with ET. Other Information Published in: eNeurologicalSci License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ensci.2022.100398